The ''We-Me'' Culture: Marketing to Korean Consumers - CHANG, Dae Ryun (Institutional Knowledge at Singapore Management University, 2007)
This paper is a focused examination of the parallel collectivistic and individualistic tendencies of South Korean consumers. The “We-Me” concept argues that the two seemingly countervailing tendencies can actually co-exist. The paper discusses the phenomenon, its underlying causes, and the strategic implications of how to market to such consumers.